Portraits de terroristes - Caroline Guibet Lafaye (Communication)
More often than not, the only thing we know about terrorists, their motivations, and their intentions is what the press reports and releases about them. Unlike social science’s approach to these topics, it appears that the media offers very selective portraits and interpretations of the motives of violence aimed at playing up psychological factors and lumping political violence together with ordinary crime. We will examine specific cases, notably media portraits of Jean-Marc Rouillan and Islamist terrorists, to highlight these shared epistemologies of terrorism.